An adaptive diffserv approach to support QOS in network mobility nemo environment - Hussein, Loay F.; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina (AIRCC Publishing Corporation, 2020)
Network Mobility Basic Support (NEMO BS) protocol (RFC 3963) is an extension of Mobile IPv6. The NEMO BS embraced by IETF working group to permit any node in the portable network to be accessible to the Internet despite the fact the network itself is roaming. This protocol likewise Mobile IPv6 doesn’t deliver any kind of Quality of Service (QoS) guarantees to its clients. It can barely offer the same level of services (i.e. Best-Effort) to all the users without obligation to the application’s needs. This propositions a challenge to real-time applications that demand a precise level of QoS pledge. The Differentiated Services has recently come to be the most widely used QoS support technology in IP networks due to its relative simplicity and scalability benefits. This paper proposes a new scheme to provide QoS to mobile network nodes within NEMO context. The proposed scheme intends to reduce handover latency for the users of MNN as well as alleviates packet losses. The feasibility of the proposed enhancement is assessed by measuring its performance against the native NEMO BS standard protocol using NS-2 simulator. The obtained results in the simulation study have demonstrated that the proposed scheme outperforms the standard NEMO BS protocol.